The timing of daily demand for goods and services: Multivariate probit estimates and microsimulation results for an aged population with German time use diary data - Joachim Merz; Dominik Hanglberger; Rafael Rucha (Leuphana Universität Lüneburg, Forschungsinstitut Freie Berufe (FFB), 2009)
Though consumption research provides a broad spectrum of theoretical and empirical founded results, studies based on a daily focus are missing. Knowledge about the individual timing of daily demand for goods and services, opens - beyond a genuine contribution to consumption research - interesting societal and macro economic as well as individual personal and firm perspectives: it is important for an efficient timely coordination of supply and demand in the timing perspective as well as for a targeted economic, social and societal policy for a better support of the every day coordination of life. Last not least, the individual daily public and private living situations will be visible, which are of particular importance for the social togetherness in family and society. Our study contributes to the timing of daily consumption for goods and services with an empirical founded microanalysis on the basis of more than 37.000 individual time use diaries of the nationwide Time Budget Survey of the German Federal Statistical Office 2001/02. We describe the individual timing of daily demand for goods and services for important socio-demographic groups like for women and men, the economic situation with income poverty and daily working hour arrangements. The multivariate microeconometric explanation of the daily demand for goods and services is based on a latent utility maximizing approach over a day. We estimate an eight equation Multivariate/Simultaneous Probit Model, which allows the decision for multiple consumption activities in more than one time period a day. The estimates quantify effects on the timing of daily demand by individual socio-economic variables, which encompasses, personal, household, regional characteristics as well as daily working hour arrangements within a flexible labour market. The question about individual effects of an aged society on the timing of daily demand for goods and services is analyzed with our microsimulation model ServSim and a population forecast for 2020 by the German Federal Statistical Office. Main result: There are significant differences in explaining the timing of daily demand for goods compared to services on the one hand and in particular for different daily time periods. The conclusion: without the timing aspects an important and significant dimension for understanding individual consumption behaviour and their impacts on other individual living conditions would be missing. – – Obwohl die Konsumforschung ein breites Spektrum theoretisch und empirisch fundierter Ergebnisse bietet, fehlen doch Studien mit einem Fokus auf die tageszeitliche Lage des Konsums. Das Wissen über die tageszeitliche Lage der individuellen Güter- und Dienstleistungsnachfrage eröffnet - über den genuinen Beitrag zur Konsumforschung hinaus - interessante gesellschaftliche und makroökonomische, sowie auch personenbezogene und Firmenperspektiven: es ist sowohl für eine effiziente zeitliche Koordination von Angebot und Nachfrage als auch für eine an dem Ziel einer besser Zeitkoordination des Alltags orientierte Wirtschafts-, Sozial- und Gesellschaftspolitik notwendig. Nicht zuletzt, werden die täglichen individuellen Lebenssituationen öffentlich und privat sichtbar, die von einer besonderen Bedeutung für das soziale Zusammenleben in Familie und Gesellschaft sind. Unsere Studie ist ein Beitrag empirischer Beitrag (basierend auf 37.000 individuellen Zeittagebüchern der Deutschen Zeitbudgeterhebung 2001/2002) zur Forschung zur tageszeitlichen Koordinierung der Nachfrage nach Gütern und Serviceleistungen. Wir beschreiben die individuelle tageszeitliche Lage der Nachfrage nach Gütern und Dienstleistungen für wichtige sozio-ökonomische Gruppen, wie für Frauen und Männer, abhängig von der Einkommenssituation und für Gruppen unterschiedlicher Arbeitszeitregelungen. Die multivariate mikroökonometrische Erklärung von der täglichen Nachfrage nach Güten und Dienstleistungen basiert auf einem latenten Nutzenmaximierungsansatz über einen Tag. Wir schätzen ein acht-gleichungs multivariates/simultanes Probit-Modell, das eine Schätzung multipler Konsumaktivitäten, also in mehr als einer Zeitperiode pro Tag, ermöglicht. Die Schätzer quantifizieren den Einfluss individueller sozio-ökonomischer Variablen, die sowohl private, haushaltliche, regionale Eigenschaften, sowie tägliche Arbeitszeitübereinkommen in einem flexiblen Arbeitsmarkt umfassen, auf die Zeitplanung der täglichen Nachfrage. Mithilfe unseres Mikrosimulations-Modells ServSim und einer Bevölkerungs-Prognose für 2020 des Statistischen Bundesamts analysieren wir die Frage nach Effekten einer alternden Gesellschaft auf die Zeitverwendung für die tägliche Nachfrage nach Gütern und Dienstleistungen. Hauptresultat: Es gibt signifikante Unterschiede in der Erklärung der tageszeitlichen Lage der Güter- gegenüber der Dienstleistungsnachfrage und auch in der Erklärung der Nachfrage in unterschiedlichen Zeitabschnitten. Ohne diese zeitlichen Aspekte der Nachfrage würde also eine wichtige und signifikante Dimension für das Verständnis individuellen Konsumverhaltens und dessen Auswirkungen auf andere individuelle Lebensbedingungn fehlen.
Keywords: J29; D12; C25; 330; timing of daily consumption/demand for goods and services; shopping hours; consumption and service activities; German Time Budget Survey 2001/2002; time use diaries; multivariate probit estimation; microsimulation model ServSim; tageszeitliche Lage der Nachfrage nach Gütern und Dienstleistungen; Ladenöffnungszeiten; Konsum- und Dienstleistungsaktivitäten; Deutsches Zeit-Budget-Studie 2001/2002; Zeittagebücher; multivariate Probit Schätzung; Mikrosimulationsmodell ServSim; Konsumentenverhalten; Zeit; Alternde Bevölkerung; Zeitverwendung; Öffnungszeit; Deutschland